2018
DOI: 10.1186/s12887-018-1273-x
|View full text |Cite
|
Sign up to set email alerts
|

The paediatric version of Wisconsin gait scale, adaptation for children with hemiplegic cerebral palsy: a prospective observational study

Abstract: BackgroundIn clinical practice there is a need for a specific scale enabling detailed and multifactorial assessment of gait in children with spastic hemiplegic cerebral palsy. The practical value of the present study is linked with the attempts to find a new, affordable, easy-to-use tool for gait assessment in children with spastic hemiplegic cerebral palsy. The objective of the study is to evaluate the Wisconsin Gait Scale (WGS) in terms of its inter- and intra-rater reliability in observational assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…The WGS is a valuable observational tool originally destined for adult stroke patients which has been modified for children with hemiplegic cerebral palsy given that both gaits are very similar. 78 The authors have reported very high inter- and intra-observer reliability.…”
Section: Gait Balance and Movement Assessmentmentioning
confidence: 97%
“…The WGS is a valuable observational tool originally destined for adult stroke patients which has been modified for children with hemiplegic cerebral palsy given that both gaits are very similar. 78 The authors have reported very high inter- and intra-observer reliability.…”
Section: Gait Balance and Movement Assessmentmentioning
confidence: 97%
“…Other possible telerehabilitation medicine friendly gait assessments include the Edinburgh Visual Gait Analysis [31], the Modified Wisconsin Gait Scale [32,33] and modified versions of the PRS [25,26,[28][29][30]34]. These tests, as with the proposed PRS, have variable intra and inter-observer reliability.…”
Section: Spinementioning
confidence: 99%
“…Gait pattern can be impaired due to motor coordination, balance, and stability problems during walking. Additionally, there are significant differences in kinematic parameters of the hip, knee, and ankle joints, compared to healthy children [ 14 ]. For the purpose of the improvement of the dynamic gait efficiency, different types of AFO are recommended for patients with spastic hemiplegic CP [ 15 ].…”
Section: Discussionmentioning
confidence: 99%